Edukasi Tentang Penggunaan Model Jamban Terapung Di Kampung Yobeh Distrik Sentani Kota Kabupaten Jayapura - Arwimbar, Petrus Y.I; Zainuri , Agus; Batmanlusi, Karel (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Indonesia is the second-largest country in the world where its population still practices open defecation (OD). This leads to around 150,000 Indonesian children dying each year due to various diseases caused by poor sanitation. Yobeh Village is one of the villages located on the shores of Lake Sentani in Jayapura District, Jayapura Regency. The purpose of this community service is to provide education on the use of the Floating Toilet Model to reduce environmental impacts and prevent the spread of diseases in Yobeh Village, Sentani District, Jayapura City, Jayapura Regency. The method used is socialization and a question-and-answer approach. The results of the socialization showed an increase in knowledge, as the community responded well and shared the issues they had been facing, such as the health impacts of open defecation. The awareness of the community changed, and they began to realize the importance of using a proper toilet (Floating Toilet). Community participation showed high enthusiasm with many questions and responses from the participants, creating a dialogue between the presenter/speaker and the residents. This activity successfully improved the knowledge, awareness, and participation of the community regarding the importance of using toilets in the lake area.